Evaluation of fecal immunoassays for canine Echinococcus infection in China. - Liying Wang; Qian Wang; Huixia Cai; Hu Wang; Yan Huang; Yu Feng; Xuefei Bai; Min Qin; Sylvie Manguin; Laurent Gavotte; Weiping Wu; Roger Frutos (Public Library of Science (PLoS), 2021)
Human echinococcosis is present worldwide but it is in China that disease prevalence is the highest. In western China, especially in the Tibetan Plateau, the burden of echinococcosis is the most important. Dogs are a major definitive host of Echinococcus and monitoring the presence of Echinococcus worms in dogs is therefore essential to efficiently control the disease. Detection kits based on three different technologies including sandwich ELISA, (indirect) ELISA, and gold immunodiffusion, are currently marketed and used in China. The objective of this work was to assess the efficacy of these kits, in particular with respect to sensitivity and specificity. Four fecal antigen detection kits for canine infection reflecting the three technologies were obtained from companies and tested in parallel on 220 fecal samples. The results indicate that the performance is lower than expected, in particular in terms of sensitivity. The best results were obtained with the sandwich ELISA technology. The gold immunofiltration yielded the poorest results. In all cases, further development is needed to improve the performance of these kits which are key components for the control of echinococcosis.